Mempromosikan Objek Wisata dan Penginapan di Pamengpeuk Melalui Teks Fungsional Bahasa Inggris - Anne Ratna Suminar; Setia Muljanto; Pipih Setiawati; Amir Hamzah (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2018)
The demand for increased foreign exchange especially in remote areas, can be obtained from tourism objects that are visited by many local and foreign tourists. To attract the foreign tourists in particular, the tourism objects may require street signs, brochures, pamphlets, or information boards written in English to make the foreign tourists visiting the tourism objects understand easily the information related to the tourism objects. Therefore, this community service program was necessarily held in two main objectives: (1) socializing the importance of using brochures and pamphlets written in English in order to attract more foreign tourists; and (2) providing workshop to recognize language features in functional texts which should be used in the brochures or pamphlets. As many as 10 hostel owners around tourism objects in Pamengpeuk followed this community service program. The methods used were lecture and training provided to the participants in the form of workshop. The findings of the community service program showed that there was no brochures or pamphlets written in English found in the hostels around tourism objects in Pamengpeuk. Furthermore, the results of the workshop revealed that 60% of hostel owners were enthusiastic in learning to write brochures in English and encouraged to make one during the workshop. However, the rest of them appeared not interested and believed that without making brochures in English the hostels still gained profits and visitors from local tourists and foreign tourists. Thus, the socialization for the importance of making brochures in English to promote tourism objects and hostel in remote areas needs to be followed up again in the next community service program.